please help me in solving this question
Attachments:
![](https://hi-static.z-dn.net/files/d99/4ac9f5bb10bd89c8d2835582fbefc460.jpg)
Answers
Answered by
2
Step-by-step explanation:
b) (x-10)(x+5)=x^2+5x-10x-50
=x^2-5x-50
c) (x+6)(x-12)=x^2-12x+6x-72
=x^2-6x-72
d) (x-7)(x-7)=(x-7)^2=x^2-14x+49
e) (x-15)(x-10)= x^2-10x-15x+150
=x^2-25x+150
hope it helps you..
Similar questions
Hindi,
5 months ago
Social Sciences,
5 months ago
Hindi,
5 months ago
Math,
11 months ago
Math,
1 year ago
Political Science,
1 year ago
English,
1 year ago